Hubungan Pemberian Tablet Fe Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Wanita Risiko Anemia - Wayan Gede Mahisa Taruna; Ida Ayu Made Mahayani; Aulia Mahdaniyati S.; Adib Ahmad Shammakh (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Iron deficiency anemia is anemia arising from reduced iron supply for erythropoesis. Anemia can pose a risk to young women both long-term and short-term. One of the efforts that the government has made to overcome the problem of anemia in adolescents is through the provision of Fe tablet supplements in the form of iron. Objective s: Knowing the relationship between Fe tablets to increasing hemoglobin levels in adolescent women at risk of anemia at the Klungkung Health Center 1, Klungkung Regency. Menthod: Observational analytical quantitative research with cross sectional study research design. The sampling technique uses purposive sampling. The study was conducted in the coverage area of Puskesmas Klungkung 1 in December 2022- January 2023. The study sample was 91 respondents. The data obtained were analyzed with the chi square test. The limit of significance values is (p < 0.05). Result: In 91 female adolescent respondents who experienced an increase in hemoglobin levels as many as 56 respondents. The results of the bivariate analysis showed that the p-value < 0.05 (p-value = 0.00). Conclution: There is a significant relationship between giving Fe tablets to increasing hemoglobin levels in adolescent women at risk of anemia at the Klungkung Health Center 1, Klungkung Regency.